Quantification of Allyl Methyl Sulfide, Allyl Methyl Sulfoxide, and Allyl Methyl Sulfone in Human Milk and Urine After Ingestion of Cooked and Roasted Garlic - Qin, Wen; Huber, Katrin; Popp, Moritz; Bauer, Patrick; Buettner, Andrea; Sharapa, Constanze; Scheffler, Laura; Loos, Helene M. (Frontiers in Nutrition, 2020)
Due to its characteristic flavor and positive effects on human health, garlic is a highly valued food ingredient. Consumption of garlic alters the quality of body odors, which may in some instances hinder social interaction but be beneficial in other contexts, as it is assumed to contribute to early flavor learning in the breastfeeding context, for example. In previous work, allyl methyl sulfide (AMS) has been identified as the major odor-active metabolite in urine and milk, being excreted together with the odorless metabolites allyl methyl sulfoxide (AMSO) and allyl methyl sulfone (AMSO2) after ingestion of raw garlic. The present work aimed to elucidate whether commonly used culinary thermal processing steps influence the excretion profiles of garlic-derived compounds. To this aim, urine (n = 6) and milk (n = 4) samples were donated before and after ingestion of roasted and cooked garlic and investigated by gas chromatography-olfactometry/mass spectrometry, and, in the case of milk, by aroma profile analysis. The concentrations of AMS, AMSO and AMSO2 were determined by stable isotope dilution assays. Sensory evaluations revealed that a garlic-like odor was perceivable in milk samples donated after ingestion of roasted and cooked garlic. Besides AMS, AMSO and AMSO2, no other odor-active or odorless compounds related to the ingestion of roasted or cooked garlic were detected in the urine and milk samples. Maximum concentrations of the metabolites were detected around one to two hours after garlic intake. In some cases, a second maximum occurred around 6 hours after ingestion of garlic. The cooking procedure led to a more important reduction of metabolite concentrations than the roasting procedure. These findings suggest that intake of processed garlic leads to a transfer of odor-active and odorless metabolites into milk, which contributes to early flavor learning during breastfeeding and may also have a physiological effect on the infant.